Evaluation of the quality of online patient information at the intersection of complementary and alternative medicine and hypertension - Ng, Jeremy Y.; Jomy, Jane; Vacca, Alexandra (Clinical hypertension, 2022)
Background Hypertension impacts 1.1 billion people globally; many patients seek complementary and alternative medicine (CAM), as a result of adverse side effects from antihypertensive medications or because they believe natural options are safer. The internet is increasingly playing a role in patient health information-seeking behavior, however, the variability of information quality across websites is unclear. Thus, the purpose of this study was to assess the quality of websites providing consumer health information at the intersection of hypertension and CAM. Methods Four unique terms were searched on Google, across Australia, Canada, the US, and the UK. The first 20 webpages resulting from each search were screened for eligibility, and were included if they contained consumer health information relating to CAM therapies for the treatment/management of hypertension. To assess the quality of health information on eligible websites, we used the DISCERN instrument, a standardized quality index of consumer health information. Results Of 90 unique webpages, 40 websites were deemed eligible and quality assessed. The 40 eligible websites were classified into seven categories: professional ( n = 15), news ( n = 11), non-profit ( n = 5), health portal ( n = 3), commercial ( n = 2), government ( n = 1), and other ( n = 3). The mean summed DISCERN score was 52.34 (standard deviation [SD] = 10.69) out of 75 and the mean overall score was 3.49 (SD = 0.08) out of 5. A total of 10 websites had a total DISCERN score of 60.00 and above with an average rating of 4.33. Among these, Medicine Net (69.00) and WebMD (69.00) were determined to have the highest quality information. Websites generally scored well with respect to providing their aims, identifying treatment benefits and options, and discussing shared-decision making; websites generally lacked references and provided inadequate information surrounding treatment risks and impact on quality of life. Conclusions While some websites provided high-quality consumer health information, many others provided information of suboptimal quality. A need exists to better educate patients about identifying misinformation online. Healthcare providers should also inquire about their patients’ health information-seeking behavior, and provide them with the guidance necessary to identify high-quality resources which they can use to inform shared-decision making.